CDK6 Is a Potential Prognostic Biomarker in Acute Myeloid Leukemia - Liu, Wei; Yi, Jin-Mou; Liu, Yi; Chen, Cong; Zhang, Kai-Xuan; Zhou, Cheng; Zhan, Hui-En; Zhao, Liang; Morales, Stephanie; Zhao, Xie-Lan; Zeng, Hui (Frontiers in Genetics, 2021)
Acute myeloid leukemia (AML) is a threatening hematological malignant disease in which new successful approaches in therapy are needed. Cyclin-dependent kinase 6 (CDK6), a regulatory enzyme of the cell cycle that plays an important role in leukemogenesis and the maintenance of leukemia stem cells (LSC), has the potential to predict the prognosis of AML. By analyzing public databases, we observed that the mRNA levels of CDK6 were significantly overexpressed in AML cell lines and non-APL AML patients when compared to healthy donors. Furthermore, CDK6 expression was significantly reduced in AML patients who achieved complete remission (CR) compared to the time of diagnosis in our validated cohort. The expression of CDK6 was tightly correlated with peripheral blood blasts, FAB subtypes, CCAAT-enhancer-binding protein α (CEBPA) mutation and chromosomal abnormalities of t(8;21). However, the clinical significance and effects of CDK6 expression on the prognosis of non-APL (Acute promyelocytic leukemia) AML patients remain uncertain. We found that CDK6 expression was inversely correlated with overall survival (OS) among non-APL AML patients using the Kaplan Meier analysis. CDK6 was also found to be positively associated with genes identified to contribute to the development of leukemia, including CCND2, DNMT3B, SOX4, IKZF2. As well as being negatively associated with anti-cancer microRNAs, including miR-187, miR-9, miR-582, miR708 and miR-362. In summary, our study revealed that CDK6 might be a potential diagnostic and prognostic biomarker in non-APL AML patients.